2018
DOI: 10.1177/1357633x18797181
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of virtual visit versus traditional clinic for management of varicose veins

Abstract: Introduction The objective of this study is to compare the clinical outcomes of patients with varicose veins managed in the telemedicine clinic and traditional clinic. Methods Retrospective analysis of all vein procedures in the institutional Vascular Quality Initiative Varicose Vein Registry (VQI VVR) was performed from January 2015 to August 2017. Patients were divided into two groups: Telemedicine versus Traditional Clinic. Comparison data included patient demographics, past medical history, clinical outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“… 20 Similarly, publications from other specialties such as general surgery (after cholecystectomies and hernia repairs) have shown safe and equally effective post-operative outpatient visits with telehealth technology compared to in-person visits. 21 Some authors have argued that expedited virtual follow-up visits might identify risk factors for re-admission of discharged patients thus improving overall care outcome. 22 …”
Section: Discussionmentioning
confidence: 99%
“… 20 Similarly, publications from other specialties such as general surgery (after cholecystectomies and hernia repairs) have shown safe and equally effective post-operative outpatient visits with telehealth technology compared to in-person visits. 21 Some authors have argued that expedited virtual follow-up visits might identify risk factors for re-admission of discharged patients thus improving overall care outcome. 22 …”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have reported that virtual clinics are associated with high patient/physician satisfaction [6][7][8]25,26], and findings have supported the effectiveness of virtual consultations in various practices [27][28][29][30][31][32][33][34]. Although teleconsultations or virtual clinics are not novel concepts, the growth of this type of health care service was slow in Taiwan owing to restrictive regulations prior to the COVID-19 pandemic.…”
Section: Comparison With Existing Literaturementioning
confidence: 97%
“…Owing to its advantages, the development, deployment, and use of telemedicine have surged in the United States [10] and other developed nations [11]. Recent studies have shown that telemedicine interventions effectively improve clinical outcomes [12], decrease costs by reducing expensive inpatient service utilization [13], and provide a superior patient experience [14], particularly in the areas of chronic disease management, such as diabetes [15], chronic heart diseases [16], thyroid disorders [17], varicose veins [18], stroke [19], mental and emotional health issues [20], and sexually transmitted diseases [21]. Previous research has also discussed the benefits, drawbacks, and barriers to the adoption of telemedicine.…”
Section: Telemedicine Backgroundmentioning
confidence: 99%